Deterministic optimization of the thermal Unit Commitment problem: A Branch and Cut search - Marcovecchio, Marian G. (2014)
This paper proposes a novel deterministic optimization approach for the Unit Commitment (UC) problem, involving thermal generating units. A mathematical programming model is first presented, whichincludes all the basic constraints and a set of binary variables for the on/off status of each generator ateach time period, leading to a convex mixed-integer quadratic programming (MIQP) formulation. Then,an effective solution methodology based on valid integer cutting planes is proposed, and implementedthrough a Branch and Cut search for finding the global optimal solution. The application of the pro-posed approach is illustrated with several examples of different dimensions. Comparisons with other mathematical formulations are also presented.